Uptake of 18FDG by a Hepatic Adenoma on Positron Emission Tomography - J. A. Stephenson; T. Kapasi; O. Al-Taan; A. R. Dennison (Case Reports in Hepatology)
Fluorodeoxyglucose positron emission tomography (18FDG-PET) is currently the best noninvasive test to confirm hepatic metastases when diagnostic uncertainty exists after initial imaging with first-line modalities. However, we report the second case of “false-positive” uptake of 18FDG on PET scanning from a histopathologically confirmed hepatic adenoma.